Keseimbangan Antara Ibadah dan Tanggungjawab Sosial Menurut Yesaya 1:10-17 - Sitompul, Ardin; Mapule, Ashar (Vieka Wahana Semesta, 2025)
This research aims to contribute to the development of a holistic understanding of worship theology, which integrates spiritual and social dimensions in the life of believers and encourages churches in Indonesia to play an active role in fighting for justice and truth in a pluralistic society. The research uses a qualitative descriptive method with a literature study approach. The research findings show that in Isaiah 1:10-17 there are three interrelated theological implications relevant to the current context of churches in Indonesia, namely the integration of worship with social ethics, holistic transformation in repentance, and social justice as a concrete manifestation of faith. Thus, this presents a new paradigm in understanding the relationship between religious rituals and social responsibility. These findings provide important contributions to the development of contextual theology in Indonesia, particularly in responding to various social injustice issues that still persist.